Simulation of shale oil flow patterns considering rock and fluid properties - LI Meng, WANG Wendong, SU Yuliang, ZHANG Jian, FAN Zhenning, LIANG Haining (Youqicang pingjia yu kaifa)
With the development of fractured horizontal well technology, shale oil exhibits great exploration and development potential. Compared with conventional oil and gas reservoirs, shale reservoirs are characterized by extremely low porosity and permeability, abundant organic matter, strong stress sensitivity, well-developed laminated structure, and diverse fluid occurrence states. Previous studies on shale oil flow patterns have typically focused on individual characteristics, inevitably leading to an incomplete understanding. This study aims to further explore the coupling mechanism of different factors on the shale oil flow patterns, thereby providing theoretical support for the efficient exploitation of terrestrial shale oil.A novel model was established to accurately characterize the oil flow patterns in shale reservoirs, integrating vertical heterogeneity and stress sensitivity of shale formation, as well as considering the adsorption-desorption effects of shale oil. The boundary conditions were simplified based on the shale oil reservoir properties to ensure both the calculation efficiency and accuracy. Taking laminated shale reservoirs—a primary target for exploitation—as a case study, the physical process of shale oil flowing from the matrix to the hydraulic fracture was investigated systematically using the proposed model. The seepage mechanism of shale oil during primary depletion was clarified, and the combined influence of vertical crossflow and formation stress sensitivity on the production of free oil and adsorbed oil was discussed. Subsequently, the proposed model was applied to the Paleogene Kong-2 member shale in the Cangdong Sag, revealing significant differences in oil production among different lithofacies and further predicting their respective production trends. Practical development strategies for shale oil were formulated based on lithofacies-dominated production characteristics.Neglecting the vertical heterogeneity in shale formations and adsorption-desorption effects of shale oil may significantly distort simulation results, leading to inaccurate shale oil production predictions. Comprehensive analyses through numerical simulations and field case studies demonstrated that: (1) During the primary depletion, well-developed laminated structures enhanced shale oil recovery. Free oil primarily migrated through laminated channels, while adsorbed oil benefited from accelerated desorption within these structures. (2) In laminated shale reservoirs, free oil mainly migrated from the shale matrix to hydraulic fractures in shale layers, and it mainly exited through sand layers. This established shale layers as oil sources and sand layers primarily as flow channels. (3) The strong stress sensitivity of shale layers enhanced oil recovery, while that of sand layers exerted adverse effects, with shale layers dominating during mid-to-late production stages and sand layers influencing early stages most significantly. The proposed model accurately simulated the physical process of oil flowing from the shale matrix to hydraulic fractures. The simulation results showed strong consistency with field observations, validating the model’s applicability for shale formation development planning and optimization.Numerical simulations investigated the shale oil flow patterns in laminated shale reservoirs by incorporating rock and fluid properties. The proposed model was utilized to characterize vertical crossflow and the desorption process of adsorbed oil in shale formations, while quantitatively evaluating the significant effects of laminated structure and stress sensitivity on shale oil production. These findings provide crucial insights for enhancing recovery in continental shale formations.